Space‐time ambiguity functions for electronically scanned ISR applications. Issue 5 (25th May 2015) - Swoboda, John; Semeter, Joshua; Erickson, Philip
Abstract Electronically steerable array (ESA) technology has recently been applied to incoherent scatter radar (ISR) systems. These arrays allow for pulse‐to‐pulse steering of the antenna beam to collect data in a three‐dimensional region. This is in direct contrast to dish‐based antennas, where ISR acquisition is limited at any one time to observations in a two‐dimensional slice. This new paradigm allows for more flexibility in the measurement of ionospheric plasma parameters. Multiple ESA‐based ISR systems operate currently in the high‐latitude region where the ionosphere is highly variable in both space and time. Because of the highly dynamic nature of the ionosphere in this region, it is important to differentiate between measurement‐induced artifacts and the true behavior of the plasma. Often, three‐dimensional ISR data produced by ESA systems are fitted in a spherical coordinate space and then the parameters are interpolated to a Cartesian grid, potentially introducing error and impacting the reconstructions of the plasma parameters. To take advantage of the new flexibility inherent in ESA systems, we present a new way of analyzing ISR observations through use of the space‐time ambiguity function. The use of this new measurement ambiguity function allows us to pose the ISR observational problem in terms of a linear inverse problem whose goal is the estimate of the time domain lags of the intrinsic plasma autocorrelation function used for parameter fitting. The framework allows us to explore the impact of nonuniformity in plasma parameters in both time and space. We discuss examples of possible artifacts in high‐latitude situations and discuss possible ways of reducing them and improving the quality of data products from electronically steerable ISRs.